Generasi Z Siap Menjadi Pengusaha Sejak Dini - Kenzie Erriezrano; Fadia Az Zahra; Suchi Octavia; Veta Lidya Delimah Pasaribu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Rapid technological developments have had a major impact on various aspects of life, including the business world. Generation Z, born between 1997 and 2012, grew up as a generation familiar with digital technology, giving them great potential to develop an entrepreneurial spirit from an early age. This Community Service Activity (PKM) aims to provide students with an understanding of the importance of entrepreneurship from an early age, foster creative and independent thinking, and utilize technology as a means to start a business. This activity was carried out at Pelita Bangsa Global Islamic School through direct guidance, interactive discussions, and question and answer sessions to determine the extent of students' understanding of the material presented. The results of the activity showed that students were very enthusiastic and understood that a business does not have to start from something big, but can come from a simple idea or hobby that is developed. They also realized that technology plays an important role in promoting and developing a business. Although there are still challenges such as lack of confidence and minimal experience, this activity succeeded in fostering an entrepreneurial spirit in the younger generation and encouraging them to dare to take advantage of opportunities from an early age.